The effect of ambient temperature on the anti-D assay using the Auto Analyzer. Issue 5 (May 1974) - Gunson, H. H.; Phillips, P. K.; Stratton, F.
Abstract : Using the AutoAnalyzer, the percentage agglutination effected by the anti-D antisera studied showed a varied dependence on the ambient temperature over the manifold subsequent to the incubation period at 37°C. This leads to assays which are a function of the ambient temperature. It is suggested that the entry of a relatively large volume of rouleaux-dispersing agent results in an elution of bound antibody to a new position of equilibrium, the shift being dependent on the particular equilibrium constant of the antibody and the rate of its attainment on the ambient temperature. A constant ambient temperature will lead to greater accuracy of anti-D assay.